An integrated decision making approach for the selection of battery recycling plant location under sustainable environment. (1st January 2022) - Sherif, S. Umar; Asokan, P.; Sasikumar, P.; Mathiyazhagan, K.; Jerald, J.
Abstract: Growing economic crisis and strict government policies and regulations regarding the environment have forced the battery industries to practice the recycling process for both economic and environmental benefits. Moreover the consideration of sustainability issues makes the recycling process more significant, successful implementation of recycling activity in the battery industry requires several strategic decisions. Among these decisions, a complex decision faced by the management is to identify the suitable location for the establishment of a formal Battery Recycling Plant (BRP). In this research work, a three-stage hybrid methodology with the combination of ISM (Interpretive Structural Modeling), fuzzy AHP (Analytic Hierarchy Process), and fuzzy COPRAS (Complex Proportional Assessment of Alternatives) methods was proposed to select the best sustainable location from the available options for BRP in India. In this study, a total of eight experts were selected from both academia and industry. Initially in this paper, 4 main sustainable criteria and 20 sustainable sub-criteria were considered from the literature review and field visits along with experts' opinions for evaluation of alternatives. This work contains three stages. In the first stage, the ISM method was used to filter 18 important sustainable sub-criteria from the primary list of 20 sub-criteria, based on its higher driving power. Then, fuzzy AHP was applied in the second stage to compute the criteria weights. In the last stage, the fuzzy COPRAS was used to rank and choose the best sustainable location for BRP. The findings emphasize that the Environmental protection level, Distance from residential areas, Distance from water source, Capital investment, Government policies, Social acceptance, Availability of scrap batteries, and Availability of utilities were the most significant criteria in the sustainability dimension. Thus, the present work helps the management in the selection of an appropriate sustainable location for BRP. Graphical abstract: Image 1 Highlights: A hybrid methodology was proposed for selecting battery recycling plant location. Sustainable criteria are considered for decision making. Interpretive Structural Modeling was used to identify the noteworthy criteria. Fuzzy Analytic Hierarchy Process was applied to obtain the criteria weights. Fuzzy Complex Proportional Assessment of Alternatives was used to select location.